2012
DOI: 10.1590/s1678-77572012000200019
|View full text |Cite
|
Sign up to set email alerts
|

Internal fit of two all-ceramic systems and metal-ceramic crowns

Abstract: Objectives The aim of this study was to investigate the internal fit (IF) of glass-infiltrated alumina (ICA - In-Ceram Alumina), yttria-stabilized tetragonal zirconia polycrystals (Y-TZP - IPS e.max ZirCAD), and metal-ceramic (MC - Ni-Cr alloy) crowns. Material and Methods Sixty standardized resin-tooth replicas of a maxillary first molar were produced for crown placement and divided into 3 groups (n=20 each) according to the core material used (metal, ICA or Y-TZP). The IF of the crowns was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1
6

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 27 publications
0
48
1
6
Order By: Relevance
“…The replica technique is accepted as a reliable and non-invasive means to determine the in vivo adaptation of crown-to-tooth surfaces. 20,[23][24][25][26] A modification of the previously described technique in the handling and stabilisation of the replicated silicone layer was used. The misfit replicated space is thin and fragile, with a thickness ranging from 20to 150 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replica technique is accepted as a reliable and non-invasive means to determine the in vivo adaptation of crown-to-tooth surfaces. 20,[23][24][25][26] A modification of the previously described technique in the handling and stabilisation of the replicated silicone layer was used. The misfit replicated space is thin and fragile, with a thickness ranging from 20to 150 mm.…”
Section: Discussionmentioning
confidence: 99%
“…To register the space between the inner surface of the copings and the abutment, a modified replica technique was applied 11,12,[22][23][24][25][26] : 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 Fig. 1 -Stereolithographic cast produced by rapid prototyping.…”
Section: Fit Recordingmentioning
confidence: 99%
“…Nevertheless, the potential influence of using plastic trays flexible or rigid cannot be excluded and therefore caution should be exercised when extrapolating the obtained results. The in vivo replica technique employed in this study is accepted as a reliable and a non-invasive method to determine the adaptation of crown-to-tooth surfaces [19,[21][22][23]. The misfit between the crown and the abutment was replicated using a modification of a previously described technique advocated for the handling and stabilization of this replicated silicone layer [27].…”
Section: Discussionmentioning
confidence: 99%
“…If the contact point was heavy, it was adjusted until crown was completely seated, and flossing was possible with light click. To document the space between the inner surface of the copings and the abutment tooth, an in vivo replica technique was applied [9,[20][21][22][23]. The crowns were first filled with a low viscosity silicone (Express™2 Ultra-Light Body Quick, 3M ESPE) seated on their corresponding preparation tooth and held in place with maximum finger pressure to simulate clinical crown cementation.…”
Section: Fit Recordingmentioning
confidence: 99%
“…Colpani et al [4] found a narrow space in the occlusal area of CAD/CAM zirconia copings (45.2 and 55.2 m). An average occlusal space centered on 100-250 m is quite common in the recent literature [5][6][7][8][9][10][11][12]. However, variable occlusal misfits, of 24 m and 634 m beneath cusp tips and central fossa [13] and as large as 1316 m [14], have also been reported.…”
Section: Introductionmentioning
confidence: 99%